Measuring Potassium Level in Packed Red Blood Cells Before Using: Word of Caution for Congenital Cardiac Surgery - Altun, Dilek; Arnaz, Ahmet; Dogan, Abdullah; Yalcinbas, Yusuf; Turkoz, Riza; Altun, Demet; Abdullah, Taner; Ozgen, Zehra Serpil Ustalar; Toraman, Fevzi; Sarioglu, Tayyar (LIPPINCOTT WILLIAMS \& WILKINS, 2021)
17th World Congress of Anaesthesiologists (WCA), ELECTR NETWORK, SEP 01-05, 2021